Penerapan Gaya Belajar melalui Layanan Bimbingan Klasikal untuk Meningkatkan Keterampilan Belajar Siswa di SMPIT Assyifa Boardingschool - Hasanah, Hasanah (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to determine the description of the learning styles of female VIII class students, before and after being given the application of classical guidance services. As well as to find out the effectiveness of the application of learning styles through classical services, the research method conducted was Classroom Action Research. Classroom action research conducted by design refers to the design of the Kemmis & Taggart model, the stages of action include (1) planning, (2) action, (3) observation, and (4) reflection. The research was conducted with two cycles. The results of the study concluded that an increase in the value or learning outcomes of students when they understand and practice learning styles means that these students have good learning skills, so it has an impact on good grades as well.